Content Analysis of Digital-Based Da'wah Bil Hikmah on Social media on the Instagram Account @dasadlatif1212 (A Study of Surah An-Nahl Verse 125) - Rahim, Abd.; Abubakar, Achmad; Basri, Halimah; Aswad, Muh. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to analyze the content of the Bil Hikmah da'wah delivered via Ustaz Das'ad Latif's Instagram social media on his Instagram account, namely @dasadlatif1212. Researchers focus on the interpretation of Surah An-Nahl verse 125 which is linked to the findings of each uploaded content. The research method used is content analysis. Researchers used this method to identify the categorization and themes used by @dasadlatif1212. Data was collected through observation of uploads spanning the period January-December 2023. Researchers found that various themes and categorizations helped convey interesting preaching. The subject's reaction in answering questions that sometimes become debatable is different from conditions that often occur. This is due to accuracy in choosing categorization and themes determined from uploads uploaded on Instagram.